Diagnostics for one-way random effects panel data models (Journal of Statistical Research, 2024)
In this paper we consider a random effects panel data model with one-way error components and derive methods for identifying outliers using the deletion technique. These outliers may be a single unit, a single time-point or a particular time-point in a particular unit. Expressions for the diagnostics for each of these three cases are derived and the technique is illustrated through an example.Journal of Statistical Research 2024, Vol. 58, No. 1, pp. 181-196.